Evaluation of the impact of continuous nursing and cluster nursing on carpal tunnel syndrome release surgery - Yang Chen; Ruihua Li; Yongqiang Zhu; Ran Chen (Journal of Orthopaedic Surgery and Research)
Abstract Background This study aimed to estimate the influence of continuous and cluster nursing on carpal tunnel syndrome (CTS) release surgery. Methods Ninety-six patients with CTS were treated in our hospital from November 2019 to December 2021. These patients were randomly divided into two groups of 48 patients. Both groups underwent open carpal tunnel release surgery. The control group received routine nursing care, while the study group received a combination of continuous and cluster nursing interventions. The Boston carpal tunnel question, the Visual Analogue Scale (VAS), the Numerical Rating Scale (NRS), the Pittsburgh Sleep Quality Index (PSQI), Disabilities of the Arm, Shoulder, and Hand questionnaire (DASH) and the Barthel index were used to compare hand function recovery, hand pain, sleep quality, and quality of life between the two groups before and 3 months after surgery. Results Both groups experienced improvements in hand function and pain 3 months after surgery. However, the study group demonstrated lower scores in symptom and dysfunction, as well as lower VAS and NRS scores compared to the control group (P < 0.05). Additionally, both groups showed an increase in the Barthel and PSQI scores 3 months after surgery. Notably, the study group exhibited higher Barthel scores and lower PSQI scores than the control group (P < 0.05). Conclusion The use of continuous and cluster nursing in patients undergoing CTS release surgery proves to be advantageous in alleviating hand pain, facilitating hand function recovery, and effectively enhancing sleep quality and overall quality of life for patients.